Common spelling errors among students of the first three grades as perceived by teachers and educational supervisors in Karak Governorate - Al- Lasasmeh, Ahlam Salem (Journal of Educational and Psychological Sciences, 2021)
The current study aimed at investigating common spelling errors for students of the first three grades as perceived by teachers and educational supervisors in Karak Governorate, as well as providing appropriate educational environments free from difficulties to develop their skills to help them know the strengths to develop them and the shortcomings to address them. The descriptive analytical approach was used, and the study sample consisted of (196) teachers and supervisors, including (176) female teachers and (20) supervisors and supervisors of Arabic language and first grades, a questionnaire was applied to them to estimate spelling errors among students, and the study concluded that the spelling errors in drawing the letters of words were above the educationally acceptable level and higher than the errors Technical spelling, which was below the educationally acceptable level.
Keywords: spelling mistakes; female teachers of the first three classes; educational supervisors